2021
DOI: 10.1111/acem.14402
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infections in children: Testing a novel, noninvasive, point‐of‐care diagnostic marker

Abstract: Objectives: Urinary neutrophil gelatinase-associated lipocalin (uNGAL) appears highly accurate to identify urinary tract infections (UTIs) when obtained via catheterization.Our primary aim was to determine the agreement in uNGAL levels between paired catheter and bag urine specimens. Our secondary aim was to compare the diagnostic test characteristics of quantitative uNGAL, dipstick uNGAL (a potential point-of-care test), and urinalysis (UA). Methods:This was a prospective study of febrile children < 24 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The risk of applicability concerns assessment of the same 25 included studies ( 5 , 36 59 ) was also performed according to the guidance of QUADAS-2. Sixteen studies were rated as having low risk of all three domain of applicability concerns ( 5 , 37 , 41 , 42 , 44 48 , 50 53 , 57 59 ). Seven studies were classified as having high risk of applicability concerns ( 36 , 38 40 , 43 , 49 , 54 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of applicability concerns assessment of the same 25 included studies ( 5 , 36 59 ) was also performed according to the guidance of QUADAS-2. Sixteen studies were rated as having low risk of all three domain of applicability concerns ( 5 , 37 , 41 , 42 , 44 48 , 50 53 , 57 59 ). Seven studies were classified as having high risk of applicability concerns ( 36 , 38 40 , 43 , 49 , 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…The forest plot shown in Figure 3A summarizes the log transformed uNGAL value in each study for the non-UTI samples reported in the pediatric studies. 16 non-UTI groups from 14 studies were included ( 37 , 39 , 40 , 42 , 44 48 , 50 , 51 , 53 , 55 , 57 ). Summarized mean and standard deviation were reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bagged urine samples exhibited lower quantitative and dipstick NGAL specificities than catheterised urine samples. 39 Other studies also established that urine NGAL expression temporally correlates with the bacterial stimulus, responds in a quantitative trend to the bacterial colony count, and rapidly reverses with the resolution of infection. [40][41][42] Furthermore, antimicrobial peptides (human α-defensin 5 [HD5] and human neutrophil peptides 1-3 [HNP1-3]) were recently evaluated for their diagnostic accuracy in children with culture-positive UTI.…”
Section: More Recent Novel Biomarkers In Urinary Tract Infection Diag...mentioning
confidence: 96%
“…43 These findings highlight, to some extent, the diagnostic utility of the biomarkers and their dependence on the urine-sampling method. 39 Urine HD5 and NGAL are more likely to correlate with UTI aetiologically attributed to E. coli than with UTI from other bacterial agents since pyuria frequently occurs in the former. 22 However, there is no consensus on the diagnostic value of these two biomarkers as they also exhibited poorer diagnostic utility in another study.…”
Section: More Recent Novel Biomarkers In Urinary Tract Infection Diag...mentioning
confidence: 99%